The Influence Of Islamic Character Education And Learning Discipline On Students’ Prosocial Behavior At Smpit As-Shofwah In Berau Regency - Fera Ayu Lestariningtyas; Paradita Purnama; Siti Hotija; Muhammad Alfi Syahrin (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
This study aims to analyze the influence of Islamic character education and learning discipline on students' prosocial behavior at SMPIT As-Shofwah in Berau Regency. Using a quantitative approach and a correlational research design, data were collected through questionnaires distributed to 37 eighth-grade students. Multiple linear regression analysis was employed to examine the relationships among the variables: Islamic character education (X1), learning discipline (X2), and students’ prosocial behavior (Y). The results indicate that Islamic character education has a significant effect on students’ prosocial behavior, with a regression coefficient of 0.819 and a significance value of 0.000 (p < 0.05). Meanwhile, learning discipline does not have a significant partial effect on students’ prosocial behavior, with a significance value of 0.112 (p > 0.05). However, simultaneous testing shows that both independent variables together have a significant effect on students’ prosocial behavior, with an R Square value of 0.716, indicating that 71.6% of the variation in prosocial behavior can be explained by these two variables.These findings highlight the importance of Islamic character education in influencing students’ prosocial behavior, while learning discipline plays a smaller role in this context. This study contributes to the development of character education in schools by emphasizing the integration of moral values and discipline in shaping positive social behavior among students.